The Influence of Google AdWords towards Homestay Marketing and Promotion in Pulau Tidung, Kepulauan Seribu - Ahmad Junaidi Abas (Budapest International Research and Critics University, 2022)
The discussion about the Google AdWords influences with the PulauTidung homestay regarding their marketing and promotion aspects as one of the top 10 Destination Ministry of Tourism priority as NTAs. The study identifies the application of their Google AdWords advertisement, the application of homestay marketing and promotion, and the correlation of Google AdWords towards homestay marketing and promotion performance. AdWords, Google’s primary search engine advertising regarding the analytics, CPC, CTR, LCR, and ROI. The homestay marketing and promotional regarding promotional activities, tour operator partnership, and web marketing. The quantitative research with correlation and regression approaches derive the hypotheses. The primary data takes the Interview and questionnaire survey. The secondary uses the behavioural data, and the combined behavioural with interview data. The Pearson Correlation highly significant correlation coefficient (0.696). The final calculation with ROI of Google AdWords operational is significantly earned with 12.5% per week. The statistical significance at α = 10%, with the Ttable (1.66). Therefore, the Ttest earns Tcalc (6.519) >Ttable (1.66) determine the Ho is rejected and Ha is accepted means Google AdWords correlates the homestay marketing and promotion performance simultaneously.